Author Guidelines - Defensoria, Revista (Revista da Defensoria Pública do Distrito Federal, 2019)
The Journal of Brazilian Federal District Public Defense receives unpublished works written in Portuguese, English, Spanish and Italian. Articles must have a minimum of fifteen (15) and a maximum of twenty five (25) pages, excluding bibliographical references, in accordance with the ABNT (Brazilian Association of Technical Norms – Associação Brasileira de Normas Técnicas) standards and the formatting rules listed below. Book reviews should be from 5 (five) to 10 (ten) pages. At the discretion of the Editor, longer or shorter texts may be published. To ensure confidentiality at the time of contribution evaluation, preserving the double-blind review, the author (s) should avoid any type of identification in the body of the text. The text should contain: a) title of the article in Portuguese (or in the language in which the text is written), maintaining direct relevance to the content of the article; b) Translation of the title into English; c) Abstract in Portuguese (or in the language in which the text is written) with a minimum of 50 (50) and a maximum of 100 (100) words; d) Five key words in Portuguese (or in the language in which the text is written); e) abstract (translation of the abstract into English); f) Five keywords (translation of key words into English); g) Bibliographical references at the end of the text, according to ABNT rules. h) The citations should be made in Author-date system. A footnote should be used for essential information to the article, which must strictly follow the ABNT standard, with font Times New Roman, size 10, single spacing, justified. i) citations should be avoided in the body of the text, especially transcriptions. Articles and revisions should note the following formatting: Sheet size: A4 Margins: left = 3 cm, right = 2,5 cm, upper = 3 cm and lower = 2,5 cm Source: Times New Roman, size 12 Line spacing: 1.5 (one and a half). Alignment: Justified. Do not place spaces between paragraphs. Title of the article / review: centralized, uppercase, bold, font size 14. The quotes should be avoided. Use it only when they are essential to the content of the contribution. They should be incorporated in the body of the text, with the use of quotation marks, when they do not exceed 3 (three) lines. If they have 4 (four) lines or more, they should be highlighted, with a 4cm indentation on the left, justified, with single line spacing and font size 11. REFERENCES For references to works cited or mentioned in the text, the author-date system must be used ABNT norms (NBR-10520). The name of the authors in the text should be made in a standardized way, mentioning their SURNAME, year of the work and page (eg SURNAME, YEAR, p.). In this system, the indication of the source is made by the last name of each author or by the name of each responsible entity until the first punctuation mark followed by the publication date of the document and the page (s) of the citation , in the case of direct quotation, separated by commas and in parentheses; FOOTNOTES AND BIBLIOGRAPHICAL REFERENCES Footnotes should be made at the bottom of the pages, according to ABNT standards. Footnotes should note the following formatting. Source: Times New Roman, Size 10, Simple Spacing, Justified. The complete references (Bibliographical references) should be presented in alphabetical order at the end of the text, increasing, also according to ABNT norms (NBR-6023). Privacy Statement The names and email addresses entered in this journal site will be used exclusively for the stated purposes of this journal and will not be made available for any other purpose or to any other party.